The cultural and religious underpinnings of moral teaching according to English language teachers' perceptions: a case study from Iran. Issue 4 (2nd October 2019) - Soleimani, Neda; Lovat, Terence
ABSTRACT: In this study, we attempt to explore a distinctive worldview as it pertains to Iranian education. We do this by focusing on the moral component implicit in English Language Teaching (ELT) in Iran and the challenges that might be experienced among ELT teachers when engaging in moral teacher practice, including making moral decisions in relation to their teaching. For this purpose, 30 ELT teachers working at Shiraz University's Language Learning Centre volunteered to describe morality in teaching and used narrative to elicit their personal stories and understandings of the challenges entailed in making moral decisions and their justifications. The article aims to determine: how ELT teachers' perceived morality is manifested in their teaching; what kinds of moral conflicts they identify in ELT; and, how they set out to resolve these conflicts. Through content analyses, we concluded that ELT teachers defined the moral component in teaching as consisting of: a balanced relationship with the learners; being on time; and, effective teaching. Moreover, they stated that mismatches between their ideologies and external codes are the biggest challenges they experience in making moral decisions. To resolve these challenges, they mostly referred to the cultural values cultivated by their religion, together with their family backgrounds, in order to justify their decisions.